Spectroscopic and electrochemical investigations of lead–lead dioxide glasses and vitroceramics with applications for rechargeable lead–acid batteries. Issue 3 (15th February 2016) - Rada, S.; Zagrai, M.; Rada, M.; Culea, E.; Bolundut, L.; Unguresan, M.L.; Pica, M.
Abstract: A new class of glass and vitroceramic electrodes with applications for rechargeable batteries was obtained by a melt quenching method. The structural characterization of the samples having the x Pb·(100− x )PbO2 composition, where x =0, 10, 20, 30, 40 and 50 mol% Pb, was performed by UV–vis and FTIR spectroscopies investigations. UV–vis and FTIR data reveal that the excess of lead content in the host matrix generates the transformation and/or disintegration of [PbO6 ] octahedral structural units into [PbO4 ] structural units or Pb 2+ ions and non-bonding oxygen ions centers. The electrochemical performances of the glass and vitroceramics electrodes were investigated by cyclic voltammetry. The shapes of the cyclic voltammograms and redox peaks depend on the electrolyte solution concentration and the lead content in host matrix. Differences between these waves are determined by the type of electrochemically active species existing in the glass or glass ceramics. The improved performance of the vitroceramic electrodes is attributed to the presence of the lead metallic phase that seems to offer an easier route for the charge process of the electrodes. Thus, the presence of these phases generates more electrochemically active species, inhibits the secondary reactions implying PbO, takes up the ionic conduction of the larger electrolyte solution and increases the charge/discharge rate of the electrochemical processes.